Collective peer scaffolding, self-revision, and writing progress of novice EFL learners - Memari Hanjani, Alireza (International Journal of English Studies, 2019)
This classroom-based study examined the effect of collective peer scaffolding activity on narrative and descriptive self-revised drafts and new paragraphs developed by 32 EFL university students in a paragraph writing course in Iran. Each genre was discussed and practiced every other week and was followed by a collective peer scaffolding session. For each genre, learners were required to develop a 150-word paragraph in two drafts (pre- and post-collective scaffolding) and email them to their lecturer within five days before the next sessions were held. They also developed a new narrative and descriptive paragraphs a month after the semester had finished. Eight volunteer students were also interviewed and their reactions to collective peer scaffolding were elicited at the end of the course. Students’ pre- and post-collective peer scaffolding drafts, new paragraphs, and interview data analysis revealed that the activity improved learners’ self-revision skill and the experience was favored by the participants.